Won't we scare them? The impact of communicating uncontrollable risks on the public's perception. Issue 3 (15th March 2016) - De Vocht, Melanie; Claeys, An-Sofie; Cauberghe, Verolien; Uyttendaele, Mieke; Sas, Benedikt
Abstract : Authorities often refrain from communicating risks out of fear to arouse negative feelings amongst the public and to create negative reactions in terms of the public's behavior. This study examines the impact of communicating risks on the public's feelings and behavioral intentions regarding an uncontrollable risk related to fresh produce. In addition, the impact of risk communication is compared between a situation in which the risk either does or does not develop into a crisis, by means of a 2 (risk communication vs. no risk communication) × 2 (crisis communication vs. no crisis communication) between-subjects factorial design. The results show that communicating risks has a positive impact on the behavioral intention to keep on eating fresh produce compared to when no risk communication was provided, as it reduces negative feelings amongst the public. In addition, the findings illustrate that when a risk develops into an actual crisis, prior risk communication can result in greater trust in the government and reduce perceived government responsibility for the crisis when the crisis hits. Based on these findings, it can be suggested that risk communication is an effective tool for authorities in preparing the public for potential crises. The findings indicate that communicating risks does not raise negative reactions amongst the public, on the contrary, and that it results in more positive perceptions of the authorities.